Konstruksi Participatory Rural Appraisal untuk Kesatuan Masyarakat Hukum Asli Berbasis Agama - Phahlevy, Rifqi Ridlo; Purwaningsih, Sri Budi; Faizin, Moh (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study discusses the renewal of the Participatory Rural Appraisal (PRA) concept based on transcendental values and its conceptual implications for empirical legal research and governance policies. PRA is a participatory rural assessment method based on the assumption that villages should be developed from within through a participatory process. The objective of this research is to develop an effective PRA concept and perspective for rural communities with a religious orientation. The research method uses a qualitative approach through description and explanation of legal phenomena and thoughts related to PRA. The findings indicate that the application of PRA in rural assessment and empowerment requires adaptation and alignment of values to maintain the existence of local values and wisdom that shape the characteristics of villages. The integration of the concept of syuro (an Islamic principle) into PRA will result in a concept that respects the participatory nature of PRA and the religious norms of the community. This concept ensures that village governance and development are guided by religious and ethical considerations, creating a more holistic and culturally sensitive approach. In conclusion, PRA adapted with transcendental values can be an effective tool in the empowerment of religious-based rural communities.